2013
DOI: 10.3346/jkms.2013.28.5.731
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Serum Autoantibodies in Idiopathic Interstitial Pneumonia

Abstract: Although autoantibodies are routinely screened in patients with idiopathic interstitial pneumonia, there are no reliable data on their clinical usefulness. The aim of this study was to investigate the prognostic value of autoantibodies for predicting the development of new connective tissue disease in these patients and also mortality. We conducted retrospective analysis of the baseline, and follow-up data for 688 patients with idiopathic interstitial pneumonia (526 with idiopathic pulmonary fibrosis, 85 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 36 publications
6
38
2
1
Order By: Relevance
“…In our study, positive ANAs were observed in 47% of NSIP and 32% of IPF patients. The observed frequency is consistent with the existing literature [25]. In our CTD-ILD patients, ANA positivity was seen in 68% which is relatively low for a CTD cohort.…”
Section: Discussionsupporting
confidence: 82%
“…In our study, positive ANAs were observed in 47% of NSIP and 32% of IPF patients. The observed frequency is consistent with the existing literature [25]. In our CTD-ILD patients, ANA positivity was seen in 68% which is relatively low for a CTD cohort.…”
Section: Discussionsupporting
confidence: 82%
“…The detection of autoantibodies may assist the diagnosis of an unrecognised CTD in specialist ILD clinics with a reported frequency of 4% to 19% [7,37,38,39]. In established CTD-ILD, autoantibodies can also allow more precise classification between the various CTDs presenting with similar clinical, radiological and/or histopathological features [39].…”
Section: Diagnosis Of Ctd-ildmentioning
confidence: 99%
“…However, in so-called “occult CTDs,” the clinical significance of these classifications and evidence for the usefulness of autoantibodies have not yet been established. Meanwhile, in this review, we found that patients with OP preceding RA have a greater prevalence of RF or CCP compared with previous reviews of patients with cryptogenic and secondary OP (RF, 3.4–19.7%; CCP, 4.2%) [1214]. Early identification of RA is becoming increasingly important because early therapy has been reported to preserve joint function [15].…”
Section: Discussionmentioning
confidence: 60%